2021
DOI: 10.1177/00221465211003232
|View full text |Cite
|
Sign up to set email alerts
|

“We’re a Little Biased”: Medicine and the Management of Bias through the Case of Contraception

Abstract: There is a wealth of literature demonstrating the presence of bias throughout the American health care system. Despite acknowledging such presence, however, little is known about how bias functions within medical encounters, particularly how providers grapple with bias in their patient counseling and decision-making. We explore such processes through the case of contraceptive counseling, a highly raced, classed, and gendered context. In-depth interviews with 51 health care providers reveal that providers use f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(36 citation statements)
references
References 45 publications
1
27
0
Order By: Relevance
“…Previous studies have documented biases in the healthcare system towards disproportionately limiting the fertility of disadvantaged patients (Manzer & Bell, 2021 ). Therefore, further research is also needed to ascertain if the increase in LARC use that we observed was produced by interactions centered around patient’s preferences (Dehlendorf et al, 2015 ), and if they were accompanied by unrestricted and timely access to LARC removal (Higgins et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have documented biases in the healthcare system towards disproportionately limiting the fertility of disadvantaged patients (Manzer & Bell, 2021 ). Therefore, further research is also needed to ascertain if the increase in LARC use that we observed was produced by interactions centered around patient’s preferences (Dehlendorf et al, 2015 ), and if they were accompanied by unrestricted and timely access to LARC removal (Higgins et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Political and cultural discourses about the deservedness and full citizenship of single black mothers that structure debates about resource allocation and welfare reform often center reproduction and child rearing. These discourses reverberate within prenatal and perinatal care settings where the politics of reproduction meet the material realities of pregnancy and birth care (Bridges 2011; Manzer and Bell 2021). The practice of drug testing allows providers to “do something” with their suspicion by mirroring forms of exclusion and disqualification that exist in the broader social political realm.…”
Section: Resultsmentioning
confidence: 99%
“…These findings are in line with studies that have previously examined the MII in the included countries and reflect the range of information given to contraceptive clients across sub-Saharan African countries [ 31 , 34 , 35 , 22 ]. Previous studies have found that clients who did not receive counseling on all components of the MII are more likely to discontinue their method within a year of initiating [ 26 , 36 ]. Discontinuation may be an example of women exercising autonomy over their contraception use, and it may also reflect insufficient counseling on method management prior to adoption.…”
Section: Discussionmentioning
confidence: 99%